MRI signs helpful in the differentiation of patients with anterior ischaemic optic neuropathy and optic neuritis. Issue 1 (19th July 2021) - Petroulia, Valentina Daphne; Brügger, Dominik; Hoepner, Robert; Vicini, Rino; Winklehner, Anna; Abegg, Mathias; Wagner, Franca
Abstract : Background/Aims: The aim of this study was to identify specific MRI characteristics of anterior ischaemic optic neuropathy (AION) and optic neuritis (ON) that would aid in the differentiation between these two diagnoses. Methods: We retrospectively analysed a consecutive case series including all patients with an MRI study of brain and orbit and the clinical diagnosis of either ON or AION. We examined the scans for restricted diffusion of the optic nerve, optic sheath diameter, enhancement and location of enhancement of the optic nerve and distribution of the white matter lesions. Results: Fifty patients met the inclusion criteria. We found an accuracy of 0.98 for the discrimination between AION and ON based solely on parameters extracted from MRI data. Dominance analysis to determine the most influential parameters showed that the enhancement pattern of the optic nerve and distribution of the white matter lesions had the biggest impact on the classification and led to a discrimination accuracy of 0.9 when used alone. Conclusion: In patients with an inconclusive clinical diagnosis, optic nerve enhancement pattern and distribution of white matter lesions can aid in the diagnosis and differentiation between AION and ON. Diffusion-weighted imaging did not add significant information to the diagnosis or help to differentiate between the two conditions.